English Listening Problems and the English Listening Ability of Second Year Air Cadets at Navaminda Kasatriyadhiraj Royal Air Force Academy - Futrakul, Kanyalek (CRMA Journal of Humanities and Social Sciences, 2022)
The purposes of this research were to: 1) Study the English listening problems; and 2) Study the English listening comprehension level of second year air cadets at Navaminda Kasatriyadhiraj Royal Air Force Academy by comparing the performances of air cadets studying in 7 majors. The sample group consisted of 90 air cadets at Navaminda Kasatriyadhiraj Royal Air Force Academy studying English in the Workplace course (HU201) in the second semester of the 2021 academic year. The research instruments were the TOEIC Listening Mock Test and the English Listening Problems Questionnaire. The statistics used in the research were percentage, mean, standard deviation, One-way ANOVA and Multiple regression. The findings revealed that 1) Cadets had problems with English listening, where the main causes of the problems were the speed of the listening text (when native speakers speak too fast) and unfamiliarity with the vocabulary used; and 2) The class of air cadets had varying levels of English listening ability, according to the CEFR standards, although differences in the majors had no effect on English listening ability at the statistical significance level of .05. Most cadets were at the B1 level according to the CEFR standards, that is, they are able to listen and understand texts where the speaker speaks slowly and clearly, using everyday vocabulary about self, family, trading, and news events, as well as short sentences and basic vocabulary.